ChemInform Abstract: Total Synthesis of the Monoterpenoid Indole Alkaloid (.+‐.)‐Aspidophylline A. Issue 32 (24th July 2014) - Teng, Mingxing; Zi, Weiwei; Ma, Dawei
Abstract: The 15‐step synthesis of the title compound (.+‐.)‐(I) includes an intramolecular oxidative coupling to create the tetracyclic furoindoline motif and a [Ni(cod)2 ]‐mediated cyclization to install the bridged piperidine ring.